Pengembangan Sikap Ecopreneurship Peserta Didik dalam Pembelajaran IPS Melalui Project-Based Learning - Widodo, Sigit (Universitas Pendidikan Indonesia, 2018)
AbstractThis study aims to determine the differences in the average increase in ecopreneurship attitudes of students in social studies learning through project-based learning. The research method used in this study was a quasi-experimental method, with pretest-posttest nonequivalent control group design. This research was conducted at Wado 2 Junior High School in Sumedang District in Class VII-A as the experimental class and VII-B class as the control class. The results of the experimental class showed that there were no significant differences in ecopreneurship attitudes in social studies learning after applying project-based learning and in the control class there were no significant differences in ecopreneurship attitudes of students in social studies learning applying the lecture method, and there were no differences the ecopreneurship attitude of students is significant in social studies learning between experimental classes after implementing project-based learning with a control class that applies the lecture method. Thus, it can be concluded that the implementation of project-based learning and lecture methods is not effective in developing the ecopreneurship attitudes of students in social studies learning.Keywords. social studies; project-based learning; ecopreneurship. AbstrakPenelitian ini bertujuan untuk mengetahui perbedaan rata-rata peningkatan sikap ecopreneurship peserta didik dalam pembelajaran IPS melalui project-based learning. Metode penelitian yang digunakan dalam penelitian ini adalah metode eksperimen semu, dengan pretest-postest nonequivalent control group design. Penelitian ini dilaksanakan di SMPN 2 Wado Kabupaten Sumedang pada Kelas VII-A sebagai kelas eksperimen dan kelas VII-B sebagai kelas kontrol. Hasil penelitian pada kelas eksperimen menunjukkan tidak terdapat perbedaan sikap ecopreneurship peserta didik yang signifikan dalam pembelajaran IPS setelah menerapkan project-based learning dan pada kelas kontrol menunjukkan tidak terdapat perbedaan sikap ecopreneurship peserta didik yang signifikan dalam pembelajaran IPS yang menerapkan metode ceramah, serta tidak terdapat perbedaan sikap ecopreneurship peserta didik yang signifikan dalam pembelajaran IPS antara kelas eksperimen setelah menerapkan project-based learning dengan kelas kontrol yang menerapkan metode ceramah. Dengan demikian maka dapat dikemukakan kesimpulan bahwa penerapan project-based learning dan metode ceramah tidak efektif untuk mengembangkan sikap ecopreneurship peserta didik dalam pembelajaran IPS.Kata Kunci. pembelajaran IPS; project-based learning; ecopreneurship.